Enabling new mindsets and transformative skills for negotiating and activating climate action: Lessons from UNFCCC conferences of the parties - Wamsler, Christine; Schäpke, Niko; Fraude, Carolin; Stasiak, Dorota; Bruhn, Thomas; Lawrence, Mark; Schroeder, Heike; Mundaca, Luis (Environmental science & policy, 2020)
•A mindset shift is already emerging across sectors and contexts.•It relates to new, relational modes of knowing, being and acting.•A paradigm shift has not yet happened at the collective level.•Safe spaces can function as a visible manifestation and catalyst.•A competency framework of transformative skills is presented. Technological and policy solutions for transitioning to a fossil-free society exist, many countries could afford the transition, and rational arguments for rapid climate action abound. Yet effective action is still lacking. Dominant policy approaches have failed to generate action at anywhere near the rate, scale or depth needed to avoid potentially catastrophic futures. This is despite 30 years of climate negotiations under the United Nations Framework Convention on Climate Change (UNFCCC), and wide-ranging actions at national, transnational and sub-national levels. Practitioners and scholars are, thus, increasingly arguing that also the root causes of the problem must be addressed – the mindset (or paradigm) out of which the climate emergency has arisen. Against this background, we investigate decision-makers’ views of the need for a different mindset and inner qualities that can support negotiating and activating climate action, along with factors that could enable such a mindset shift. Data were collected during participatory workshops run at the 25th UNFCCC Conference of the Parties (COP25) in 2019, and comprise surveys, as well as social media communication and semi-structured interviews with COP attendees. Our results underline vast agreement among participants regarding the need for a mindset shift that can support new ways of communication and collaboration, based on more relational modes of knowing, being and acting. They also suggest the emergence of such a mindset shift across sectors and contexts, but not yet at the collective and systems levels. Finally, they highlight the importance of transformative skills and the need for experimental, safe spaces. The latter are seen as a visible manifestation and enabler that can support agency for change through shared self-reflection, experience and practice. We present a transformative skills framework, and conclude with further research needs and policy recommendations.